"Easter Blessing" - Truman State University, Pickler Memorial Library Special Collections, University Archives (Owner, Digitizing Technician) (International Art Publishing Co., 1910)
Easter postcard with a biblical verse, lilies of the valley flowers, and two bells; addressed to Mrs. T. L. Anderson; postmarked March 23.